Tributyl phosphate as a type of environmental endocrine disruptor associated with liver fibrosis: insights from NHANES and in vitro validation - Liwei Yang; Aipeng Ju; Yawen Huang; Huibin Jiang; Jiaming Ye; Wen Qi; Liting Zhou (Frontiers in Toxicology, 2025)
BackgroundEnvironmental endocrine disruptors (EEDs) had been proved as significant risk factors for liver fibrosis. However, which specific pollutants predominantly related to liver fibrosis remain unidentified. This study was aimed to screen in the specific EEDs using NHANES data and further validate the findings in BRL-3A hepatocytes.MethodsA total of 5,843 adult participants (≥18 years) incorporating data on EEDs/metabolites, demographics, lifestyle factors, and vibration-controlled transient elastography (VCTE) measurements were gated from the NHANES. Advanced analytical methods including LASSO regression, multivariable logistic regression, and restricted cubic spline (RCS) modeling were implemented for pollutant screening. In vitro validation involved treating BRL-3A hepatocytes with identified EEDs, followed by comprehensive assessment of fibrotic markers through quantitative PCR, Western blotting, and extracellular matrix component analysis.ResultsDi-n-butyl phthalate (DBuP), the metabolites of tributyl phosphate (TBP), was demonstrated to be the strongest EEDs associated with liver fibrosis (P < 0.05). Mechanistic studies revealed that 1 μM TBP significantly elevated extracellular matrix components (HA: +130%, Ⅳ-Col: +22%) through MMP9 upregulation at both transcriptional (1.8-fold increase) and translational (1.73-fold increase) levels in hepatocytes.ConclusionOur findings establish TBP as a novel environmental determinant positively correlated with liver fibrosis in U.S. adults. The profibrotic effects appear mediated through transcriptional activation of extracellular matrix remodeling genes, particularly via MMP9 pathway modulation.